How shareholder litigation risk influences firm orientation toward stakeholders - Park, Eunyoung; Lange, Donald; Jeon, Chunhu (Strategic Management Journal, 2025)
Abstract Research Summary This study examines whether U.S. corporate executives would adopt a stronger stakeholder orientation if constraints imposed by shareholder litigation risk were relaxed. Leveraging the staggered adoption of Universal Demand (UD) laws across states as a quasi‐experimental setting, we test whether reduced litigation risk leads to managers prioritizing broader stakeholder initiatives. We find that firms increase stakeholder‐focused efforts following UD law adoption, with this shift more pronounced in firms with weaker shareholder governance provisions and lower levels of outside director ownership. Our study advances corporate governance and stakeholder theory by demonstrating how shareholder litigation risk acts as a governance mechanism that shapes managerial priorities. Additionally, we identify key boundary conditions moderating the relationship between governance constraints and stakeholder engagement. Managerial Summary What happens when corporate executives feel less constrained by the risk of shareholder litigation? This study examines how reducing litigation risk leads to managers shifting their focus toward initiatives that benefit broader stakeholder groups, including employees, communities, and the environment. Using state‐level legal changes as a natural experiment, we find that firms adopt a more stakeholder‐oriented approach when shareholder litigation risk decreases—particularly in firms with weaker governance mechanisms tied to shareholder oversight. These findings highlight the critical role of legal frameworks and governance structures in shaping how executives balance shareholder and stakeholder priorities. For practitioners, this underscores the function of governance systems in influencing a firm's stakeholder strategy.